TUC Poster - Unemployment, 1981 (1981)
1981 1960-2000 "TUC Poster - Unemployment, 1981" [T0580.jpg], 1981 Following the election of a Conservative Government in 1979, the TUC launched the Campaign for Economic and Social Advance to publicise its policies on public expenditure and services and to lay out its alternative economic and industrial strategy. In April 1981, the TUC organised a week of activities to highlight the problems of unemployment in particular regions and industries. Events included rallies in Newcastle, Norwich, Cardiff, Birmingham Belfast, Durham and Nottingham, a national demonstration protesting the state of the textiles industry in Bradford, and a Bread and Roses concert in London.